Survey on farm tractor (John Deere) total cost in field FFB evacuation: a case study in Far East Holding Berhad / Mohd Zulazriey Zulkifly and Muhammad Aliuddin Bakar - Zulkifly, Mohd Zulazriey; Bakar, Muhammad Aliuddin (Faculty of Plantation and Agrotechnology, 2018)
Estate Mechanization is becoming more important in overcoming labor shortage and enhancing labor productivity. That are more type of mechanization been used in plantation example is a farm tractor to easy the process evacuate the product from in-field to the mill). This study focus on survey the total cost in-field FFB evacuation. The study was conduct Far East Holding. Ladang Sungai Gayung. Pahang. The objective of this study is to study the total cost of FFB evacuation by tractor per year in field, factor that influence total cost of farm tractor per year and to study the effectiveness and efficiency of total cost toward the tractor operation. The farm tractor used is John Deere 5715 model. 89hp. Fixed cost like depreciation, tax and insurance not be calculated because this estate use old tractor. This study more focusing to the total operating cost which is Fuel, lubricants, repair, maintenance and labor. The higher total operating cost for year 2017 is at February which is RM 6442 because tractor was breakdown and go to workshop. Total repair for this tractor at this month is RM 5645 just for spares and RM 269, RM528 for servicing and lubricants. Based on 4 years data analysis, it shown 2017 is the highest operating cost which is RM 52273 and 2016 is the lowest operating cost with RM 37519. Based on the data analyse it shown that more life span of tractor, more expenses of total operating cost to be spent to maintain the farm tractor in good condition and to running maximize to increase the profitability of the company.